PENGARUH METODE VIDEO DAN CERAMAH TERHADAP KEMAMPUAN CUCI TANGAN ANAK PRASEKOLAH - Edy Mulyono; Amin Huda Nurarif; Esti Vera Yosa (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
The use of appropriate methods can affect the ability of respondents. The ability to wash hands is to do well how to wash hands properly using soap and running water. The purpose of the study was to determine differences in the ability of health education video methods and lectures on hand washing at TK Bunga Kasih West Kutai. The type of research used is Quasi Experiments with Nonequlvalent control group design. The study population was kindergarten children of Bunga Kasih Barong Tongkok. The sample of the respondents was 30 respondents divided into 2 groups, 15 groups of video methods and 15 respondents in the lecture method technique by consecutive sampling. The research instrument uses an observation sheet. Data were analyzed using the Wilcoxon test and the Whitney Man Test. The results obtained after being given health education the ability of the two groups of respondents there is a change evidenced by an increase in the good category. The results of the Wilcoxon statistical test obtained pvalue = 0,000 video method and pvalue = 0,0001 lectures, p 5 0,05. The Man Whitney test obtained the value of p value = 0.034 smaller than the value of α (p ≤ 0.05). The conclusion is that there is an effect of increasing handwashing ability after being given video method health education and lecture method. And the video method is more influential on increasing the ability of preschoolers to wash their hands.